NILAI RUJUKAN UNTUK EVALUASI FUNGSI HATI DAN GINJAL PADA TIKUS (Rattus norvegicus Berkenhout, 1769) GALUR WISTAR - Fitria, Laksmindra; Lukitowati, Fajar; Kristiawati, Dian (Jurnal Pendidikan Matematika dan IPA, 2019)
Evaluation of liver and renal functions are routine tests performed in preclinical studies. Liver plays a role in detoxification and secretion of various substances to regulate a wide range of metabolic functions. Kidneys serves as the main excretory and osmoregulatory organs. Thus, assessment of liver and renal functions are important in identifying the presence of damages and diseases as well as monitoring body responses towards treatments or therapy. Therefore, normal values should be established for valid reference. Until now, many researchers still use references from various publications, including foreign countries with different environmental factors and method of animals care. This study was aimed to provide reference values for liver and renal functions in male and female Wistar rats. Animals were sourced from LPPT-UGM. Age 4-, 6-, and 8-week-old represent juvenile, preadult, and adult. Blood samples were collected from orbital sinus of anesthetized animals. Sera were tested for ALT, AST, BUN, and creatinine based on spectrophotometry. Results demonstrated that values of most parameters varied, depend on sex and age. According to this finding, it can be concluded that reference values cannot be generalized but must be determined by sex and age in local population.